Unlocking Access to Finance for SMEs : A Cross-Country Analysis - Fouejieu, Armand (IMF Working Papers; Working Paper ;, 2020)
Countries in the MENAP and CCA regions have the lowest levels of financial inclusion of small and medium enterprises (SMEs) in the world. The paper provides empirical evidence on the drivers of SME access to finance for a large sample of countries, and identifies key policy priorities for these two regions: economic and institutional stability, competition, public sector size and government effectiveness, credit information infrastructure (e.g., credit registries), the business environment (e.g., legal frameworks for contract enforcement), and financial supervisory and regulatory capacity. The analysis also shows that improving credit information, economic competition, the business environment along with economic development and better governance would help close the SME financial inclusion gap between MENAP and CCA regions and the best performers. The paper concludes on the need to adopt holistic policy strategies that take into account the full range of macro and institutional requirements and reforms, and prioritize these reforms in accordance with each country's specific characteristics.